Diálogo en la enseñanza Teoría y práctica - BURBULES, Nicholas C. (AMORRORTU, 1999)
CONTENIDO : FREIRE, Paulo; BAJTIN, Mijail M.; GADAMER, H.G.; HABERMAS, J.; VIGOTSKY, L.S.; DEWEY, John; WITTGENSTEIN, L.